The onset of deep recycling of supracrustal materials at the Paleo-Mesoarchean boundary. Issue 3 (30th July 2021) - Wang, Xiaolei; Tang, Ming; Moyen, Jeff; Wang, Di; Kröner, Alfred; Hawkesworth, Chris; Xia, Xiaoping; Xie, Hangqiang; Anhaeusser, Carl; Hofmann, Axel; Li, Junyong; Li, Linsen
Abstract: The recycling of supracrustal materials, and in particular hydrated rocks, has a profound impact on mantle composition and thus on the formation of continental crust, because water modifies the physical properties of lithological systems and the mechanisms of partial melting and fractional fractionation. On the modern Earth, plate tectonics offers an efficient mechanism for mass transport from the Earth's surface to its interior, but how far this mechanism dates back in the Earth's history is still uncertain. Here, we use zircon oxygen (O) isotopes to track recycling of supracrustal materials into the magma sources of early Archean igneous suites from the Kaapvaal Craton, southern Africa. The mean δ 18 O values of zircon from TTG (tonalite–trondhjemite–granodiorite) rocks abruptly increase at the Paleo-Mesoarchean boundary (ca. 3230 million years ago; Ma), from mantle zircon values of 5‰–6‰ to approaching 7.1‰, and this increase occurs in ≤3230 Ma rocks with elevated Dy/Yb ratios. The 18 O enrichment is a unique signature of low-temperature water–rock interaction on the Earth's surface. Because the later phase was emplaced into the same crustal level as the older one and TTG magmas would derive from melting processes in the garnet stability field (>40 km depth), we suggest that this evident shift in TTG zircon O isotopic compositions records the onset of recycling of the mafic oceanic crust that underwent seawater hydrothermal alteration at low temperature. The onset of the enhanced recycling of supracrustal materials may also have developed elsewhere in other Archean cratons and reflects a significant change in the tectonic realm during craton formation and stabilization, which may be important processes for the operation of plate tectonics on early Earth. Abstract : Deep recycling of supracrustal materials and possible operation of plate tectonics started at ca. 3230 million years ago, revealed by zircon oxygen isotopes in southern Africa.